PREVALENSI PERILAKU PENCEGAHAN INFEKSI SALURAN PERNAFASAN AKUT MASYARAKAT DI PUSKESMAS GUNUNG TINGGI TAHUN 2023 - Sinurat, Samfriati; Novitarum, Lilis; Tambunan, Agustina Sabarni (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2024)
Acute respiratory infection or what is often called ISP is inflammation of the respiratory tract caused by bacteria that can be transmitted through air or droplets which is influenced by several factors including behavioral factors such as indoor smoking habits, the use of firewood for cooking and a lack of environmental awareness. Clean and healthy, inadequate ventilation and also insufficient lighting. Bad behavior can increase the spread of viruses and bacteria that can cause ARI.This study aims to determine the behavior of community ARI prevention at the Gunung Tinggi Health Center 2023. This study uses a descriptive research type with a cross sectional approach. The population in this study are people suffering from ARI at the Gunung Tinggi Health Center, totaling 2211 people. The sampling technique is purposive sampling, amounting to 92 respondents. The instrument used is a questionnaire with 34 statements of ARI prevention behavior. Based on the results of the study, it is found that the behavior of preventing ARI in the community as a whole showed 58.7% have poor behavior. The results show that the knowledge domain of ARI prevention is 56.5% good, the ARI prevention attitude domain is 60.9% poor, and the ARI prevention action domain is 76.1% poor. It is hoped that the community can raise self-awareness of the importance of health through the prevention of ARI in attitudes and actions such as banning smoking indoors, improving a clean and healthy environment.